The right of the child to work between leave and prohibition to protect him from psychological and social risks - Bouchrea, Nassima (Journal of Human Sciences, 2023)
Considering that the child is that vulnerable being, due to his incomplete mental, psychological and physical development, most international and national legislation, including Algerian legislation, has sought to protect him in various fields, in addition to ensuring his rights and dedicating them to him as a member of society, and among those rights recognized to him : His right to work with reservations about granting him this right in a way that does not conflict with protecting him from the risks he may be exposed to in this field. These risks, which may be physical risks that affect his physical development, may also be psychological risks that affect his psychological balance and his future social life. For this reason, the Algerian legislator has established strict controls and restrictions on child labor to protect them, sometimes related to determining the age, scope and times of work.